(untitled) (Research, Society and Development, 2022)
Functional foods or ingredients are characterized by offering health benefits, in addition to their basic nutritional functions. These foods are growing, as the consumer is increasingly demanding with regard to healthy eating and the quality of food ingested. Therefore, the objective of this study was to develop and sensorially evaluate a chocolate brownie-type cake with functional ingredients, in addition to evaluating the nutritional composition. The formulation of this food was composed of ingredients such as oats, cocoa and 70% chocolate, which are considered to have functional properties. For sensory evaluation, the acceptance test was used by a nine-point hedonic scale, acceptability index, in addition to the analysis of purchase intent, with the participation of 57 untrained tasters. For the nutritional calculation, the Avanutri software and the food chemical composition table were used. The results obtained showed an average overall impression of the product of 8.30, lying between the terms “I liked it very much” and “I liked it very much”, acceptance above 87% and the purchase intention index was 98.2% . The brownie developed in this study can be considered as a good source of protein and dietary fiber. Therefore, it was considered a product of great acceptance and purchase intent and that could offer functional benefits to brownie consumers due to the ingredients used in the formulation.